Pengaruh Model Pembelajaran Ball Feeling Untuk Meningkatkan Keterampilan Passing Kaki Bagian Dalam Siswa Smp - Birawa, Ahmad Dimas Candra; Cahyani, Olivia Dwi; Apriyanto, Rohmad (Universitas Hamzanwadi, 2026)
Instruction on inside foot passing in soccer at the junior high school level is often less than optimal due to students' low sensitivity (ball feeling) to the ball and the lack of variety in the instructional models used. This study aims to analyze the effect of applying the ball feeling learning model on improving inner foot passing skills in junior high school students. The study used a pre-experimental method with a One Group Pretest-Posttest Design. The sample consisted of 30 seventh-grade students from SMP Negeri 1 Sumberrejo. The research instrument was a low passing test toward the target. The data were analyzed statistically using the Paired Sample t-test and effect size calculation (Cohen's d) with the help of SPSS 25. The results showed a significant increase in students' passing ability, with a pretest average score of 5.97 increasing to 7.40 on the posttest (p = 0.000). The effect size obtained was 0.816, which is classified as a large effect, indicating a strong practical impact of the intervention. The ball feeling learning model proved to be effective and had a significant influence on improving students' inner foot passing skills in soccer. These findings recommend the integration of the ball feeling approach in teaching basic soccer techniques in junior high schools.